Impacts of spontaneous hot flow anomalies on the magnetosheath and magnetopause. Issue 4 (15th April 2016) - Omidi, N.; Berchem, J.; Sibeck, D.; Zhang, H.
Abstract: Spacecraft observations and global hybrid (kinetic ions and fluid electrons) simulations have demonstrated that ion dissipation processes at the quasi‐parallel bow shock are associated with the formation of structures called spontaneous hot flow anomalies (SHFAs). Previous simulations and recent spacecraft observations have also established that SHFAs result in the formation of magnetosheath filamentary structures (MFS). In this paper we demonstrate that in addition to MFS, SHFAs also result in the formation of magnetosheath cavities that are associated with decreases in density, velocity, and magnetic field and enhancements in temperature. We use the results of a global MHD run to determine the change in the magnetosheath properties associated with cavities due to ion kinetic effects. The results also show the formation of regions of high flow speed called magnetosheath jets whose properties as a function of solar wind Mach number are described in this study. Comparing the properties of the simulated magnetosheath cavities and jets to past spacecraft observations provides good agreement in both cases. We also demonstrate that pressure variations associated with cavities and SHFAs in the sheath result in a continuous sunward and antisunward magnetopause motion. This result is consistent with previous suggestions that SHFAs may be responsible for the generation of ion cyclotron waves and precipitation of ring current protons in the outer magnetosphere. Key Points: SHFAs result in the formation of magnetosheath cavities SHFAs result in the formation of magnetosheath jets SHFAs result in continuous in and out motion of the magnetopause